Evaluation of Ecological Resilience of Agricultural Ecosystems in Razavi Khorasan Province: Comparison of Integrated and Non-Integrated Ecosystems - Pegah Naghipour; Alireza Koocheki; Mahdi Nasiri mahalati; Soroor Khorramdel (بوم شناسی کشاورزی)
Introduction[1]Agriculture plays a very important role in the realization of many of the United Nations Sustainable Development Goals (SDGs). If agriculture is to make a positive contribution to achieving these goals, ensuring the ecological resilience of farmers i.e. improving adaptation capacity of the households as well as the whole production system to a wide range of environmental changes and shocks is crucial. The intensification of climate change caused by global warming and its consequences, including the occurrence of long droughts, floods and other natural disasters, have threatened the food security of subsistence farmers and smallholders in the first place, and the food security of large communities in the long run. Also recently, the covid-19 pandemic and the possibility of similar epidemics have created more concerns. Therefore, the issue of resilience has been highly considered by researchers and international organizations, especially the Food and Agriculture Organization of the United Nations (FAO), so that resilience has been defined as one of the 10 elements of agroecology. On the other hand, numerous research evidences have shown that integrated systems (combination of crop cultivation and animal husbandry) in order to increase structural and functional diversity, increase ecological resilience against severe environmental stresses and climate changes. In addition, integrated systems have different resilience and ecological stability depending on the intensity, amount and type of integration. Therefore, in the recent years large number of researches are conducted to address the resilience of agricultural systems. Since the ecological dimensions of resilience have not been comprehensively investigated in Iran, the purpose of this research is to evaluate the ecological resilience of rural households in Razavi Khorasan province and compare systems based on agriculture, based on livestock and integrated systems of agriculture and livestock. In this research, the recommended method of FAO has been used to evaluate resilience.Materials and MethodsThe required informations were collected from 87 households from 10 cities within the province by completing a comprehensive questionnaire and face-to-face interviews with households. Data were analyzed using RIMA II-FAO method. Clustering of 87 households based on their corresponding cultivated area of crops, saffron and the number of livestock units was resulted in 4 livelihood groups, including only cropping (G1), the integrated crop-livestock at medium level (G2), only livestock at large level (G3) and integrated crop-livestock both at large level (G4). The resilience of households in each group was evaluated based on 5 components (asset, adaptive capacity, biodiversity, intensification, and use of ecosystem services), each measured by a number of indicators. The scores of 5 components were aggregated after weighting, by using factor analysis, and normalization to develop a composite resilience index in 1-5 scale.Results and DiscussionThe results showed a significant relationship between the resilience of rural households and the 5 mentioned components where intensification had negative correlation with resilience while the impact of assets, adaptation capacity, biodiversity and use of ecosystem services on household resilience was positive with the highest correlation for biodiversity. The households of integrated crop-livestock groups (G2) and (G4) had the highest resilience compared to households in single enterprise groups i.e. only cropping (G1) and only livestock (G3), with the lowest resilience in G3. In general, the high score of the components of biodiversity, ecosystem services, adaptive capacity, as well as the low level of intensification in small to medium scale integrated crop-livestock systems resulted to more resilient households while large scale single enterprise households had lower resilience despite their higher assets.ConclusionResilience is fundamental bases of sustainability and it refers to the ability of systems to return to its initial state after facing environmental tensions. The main purpose of the present study was to evaluate ecological resilience for agriculture ecosystems of Khorason Razavi province. The main findings indicated that the integrated farmlands with other activities particularly with animal husbandry is much more resilient than pure and monotype farm production systems.AcknowledgementsWe are grateful to the Honorable Vice Chancellor of Research and Technology of Ferdowsi University of Mashhad for providing the costs of this research.